Investigation of Umrah Travel Promotion: Does It Use the MLM System? Case Study from PT. Arminareka Perdana - Fauziah Marzuki (Maliki Islamic Economics Journal, 2022)
This study aims to explain the marketing system carried out by Travel Umrah based on PMA regulation No. 8/2018. This research uses a qualitative approach through observation, literature review, and in-depth interviews with each resource person at PT. Arminareka Perdana. The analysis is descriptive by interpreting the conditions and relationships in an observation. The findings show that most umrah pilgrims misunderstand the regulatory provisions. In addition, the marketing system no longer uses a network that resembles an MLM pattern but uses a conventional system. The marketing system used by Umrah Travel is still conventional. Preferably marketing should be done using a spiritual marketing system because Umrah is a Ubbudiyyah trip.